TAM receptors in apoptotic cell clearance, autoimmunity, and cancer. (August 2013) - Nguyen, Khanh-Quynh; Tsou, Wen-I; Kotenko, Sergei; Birge, Raymond B.
<x xml:space="preserve">Abstract</x> Receptor tyrosine kinases, Tyro-3, Axl and Mer, collectively designated as TAM, are involved in the clearance of apoptotic cells. TAM ligands, Gas6 and Protein S, bind to the surfaces of apoptotic cells, and at the same time, interact directly with TAM expressed on phagocytes, impacting the engulfment and clearance of apoptotic cells and debris. The well-tuned and balanced actions of TAM may affect a variety of human pathologies including autoimmunity, retinal degeneration, and cancer. This article emphasizes some of the emerging findings and mechanistic insights into TAM functions that are clinically relevant and possibly therapeutically targeted.